Conflict over water resources: Análisis y comprensión de los actores desde su entorno - Silva Hernández, Francisca (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Water as a vital asset of all living beings, in a state of vulnerability, damage and/or risk can manifest as a socio-environmental conflict. In the mapping of the conflict, various actors are identified, however, an essential actor are the members of the community in which conflicts emerge that must be managed to lead to a consensus of common good. The exposed case study addresses and describes essential elements that must be foreseen in the management and conflict agreements between members of ejidos, communities and/or indigenous peoples from the interpretation of social and cultural language.